(untitled) (IITM Journal of Business Studies, 2024)
This paper presents a thorough investigation into the multifaceted impact of ChatGPT on academia and research, with emphasis on revolutionizing these domains through the integration of AI models. The primary objective is to develop a comprehensive survey instrument to capture various parameters and nuances associated with the influence of ChatGPT. The study engages in a thorough exploration of participants’ perspectives, examining factors such as perceived usefulness, willingness to explore innovative applications, and beliefs about the potential role of AI models in shaping academic research and publication. Ethical considerations, bias mitigation strategies, and user satisfaction are also integral components of the study.